Intermediate Russian : a grammar and workbook - Murray, John (John Damian) (Grammar workbooks., 2013)
Intermediate Russian provides a reference grammar and related exercises in one volume. Varied texts from Russian sources give an insight into contemporary Russian society and culture. Features include: * texts and exercises reflecting contemporary Russian * concise grammar explanations * full exercise key * detailed index. Intermediate Russian , and its sister volume, Basic Russian , are ideal both for independent study and use in class. Together the books provide a compendium of the essentials of Russian grammar.